Targeting Viral cccDNA for Cure of Chronic Hepatitis B - Ligat, Gaëtan (Curr Hepatol Rep, 2020)
PURPOSE OF REVIEW: Chronic hepatitis B (CHB), caused by hepatitis B virus (HBV), is a major cause of advanced liver disease and hepatocellular carcinoma (HCC) worldwide. HBV replication is characterized by the synthesis of covalently closed circular (ccc) DNA which is not targeted by antiviral nucleos(t)ide analogues (NUCs) the key modality of standard of care. While HBV replication is successfully suppressed in treated patients, they remain at risk for developing HCC. While functional cure, characterized by loss of HBsAg, is the first goal of novel antiviral therapies, curative treatments eliminating cccDNA remain the ultimate goal. This review summarizes recent advances in the discovery and development of novel therapeutic strategies and their impact on cccDNA biology. RECENT FINDINGS: Within the last decade, substantial progress has been made in the understanding of cccDNA biology including the discovery of host dependency factors, epigenetic regulation of cccDNA transcription and immune-mediated degradation. Several approaches targeting cccDNA either in a direct or indirect manner are currently at the stage of discovery, preclinical or early clinical development. Examples include genome-editing approaches, strategies targeting host dependency factors or epigenetic gene regulation, nucleocapsid modulators and immune-mediated degradation. SUMMARY: While direct-targeting cccDNA strategies are still largely at the preclinical stage of development, capsid assembly modulators and immune-based approaches have reached the clinical phase. Clinical trials are ongoing to assess their efficacy and safety in patients including their impact on viral cccDNA. Combination therapies provide additional opportunities to overcome current limitations of individual approaches.